Use of citrus pulp for biogas production: A GIS analysis of citrus-growing areas and processing industries in South Italy. (July 2017) - Valenti, Francesca; Porto, Simona Maria Carmela; Chinnici, Gaetano; Selvaggi, Roberta; Cascone, Giovanni; Arcidiacono, Claudia; Pecorino, Biagio
Abstract: Among the renewable energy sources, the production of biogas from biomass by anaerobic digestion has developed significantly in the last twenty years in Italy, especially in the North. In this field, a new concept proposes the production of biogas in a more sustainable way by a sustainable intensification of crop rotation, use of agro-industrial wastes, and recycling the nutrients of by-products used to produce biogas. Among the by-products used to extract biogas, re-using residual biomass of citrus processing industries, like citrus pulp, has been recently put forward. Given the uncertainty of data relating to biomass quantities, this research aims at filling the gap in the knowledge of the production and yield of citrus pulp for energy uses. Therefore, this study investigates the suitability of using citrus pulp as a possible matrix of the blend needed to feed anaerobic digesters in territorial areas where biogas sector is still developing. This aim is relevant to plan the development of new biogas plants in a sustainable way with regard to environmental protection, and specifically, in terms of reduction of both soil consumption for dedicated energy crop and greenhouse gas (GHG) emissions derived from biomasses logistic supply, as well as the re-use of agro-industrial wastes. On this basis, a case study was analysed by using GIS tools and descriptive statistics as well as by investigating the specific regulatory framework. The results of the statistical analyses showed that there is great variability in citrus production for the different citrus fruits because of the species specialisation of some farms and their various production capacities. The results of the GIS analyses highlighted that localisation of the citrus processing areas is highly concentrated in specific geographic areas. Therefore, it would be desirable that the future policies of development of biogas sector, take into account the availability and distribution of agricultural biomasses in the territory. Finally, the regulatory framework was found of crucial importance in supporting or inhibiting the utilisation of the biomass in a specific sector, with regard to the case study considered.